2012
DOI: 10.1159/000343669
|View full text |Cite
|
Sign up to set email alerts
|

Most Important Chronic Complications of Arteriovenous Fistulas for Hemodialysis

Abstract: The aim of this review was to highlight the most important complications of arteriovenous fistulas (AVFs) for hemodialysis (HD). The quality of vascular access for HD should be suitable for repeated puncture and allow a high blood flow rate for high-efficiency dialysis with minimal complications. The dialysis staff must be well versed in manipulation of the AVF, and there should be a minimal need for corrective interventions. Construction of an AVF creates conditions for increasing the flow of blood through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
2
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 77 publications
(101 reference statements)
1
114
2
20
Order By: Relevance
“…Several studies have shown that patients who received treatment in outpatient dialysis facilities were at a high risk of developing infections, probably due to multiple factors such as the need for repeated vascular access through central venous catheters, arteriovenous grafts, or fistulas, and also frequent hospital visits and frequent receipt of antimicrobial drugs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that patients who received treatment in outpatient dialysis facilities were at a high risk of developing infections, probably due to multiple factors such as the need for repeated vascular access through central venous catheters, arteriovenous grafts, or fistulas, and also frequent hospital visits and frequent receipt of antimicrobial drugs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, retrograde flow in the radial artery occurs in more than 70% of patients with AVF, which, however, does not cause ischemia in subjects with normal blood circulation [15] . Ischemic syndrome in physiological conditions results from a fall in blood pressure in the periphery and failure of compensatory vasodilatation [16] . Heart failure in HD patients has a multifactorial character [14,[17][18][19] .…”
Section: Hemodynamic Impact On the Development Of Distal Ischemiamentioning
confidence: 99%
“…An AAVF not meeting these criteria has an increased risk of failure and further investigations may be required. 10 Several studies indicate that about 30% of hospitalisations are caused by the constriction and complications of vascular access. 11 Both artery and vein undergo marked changes in haemodynamic forces following creation of an AAVF resulting in vascular remodelling.…”
Section: Discussionmentioning
confidence: 99%